Requirement of ONE-HELIX PROTEIN 1 (OHP1) in early Arabidopsis seedling development and under high light intensity. (2nd December 2018) - Hey, Daniel; Grimm, Bernhard
ABSTRACT: Plant ONE-HELIX PROTEINS (OHPs) are part of the light-harvesting complex superfamily whose members are involved in various processes related to sensing and capturing light as well as light protection. We recently showed the requirement of a functional OHP1-OHP2 heterodimer for efficient D1 synthesis. Interestingly, while the ohp1 knockout mutant showed a strong defect in accumulation of the photosystem II and is hardly viable, virus-induced gene silencing of OHP1 had no detectable impact on plant growth and performance under standard growth conditions. However, in vivo labeling assays with 35 S-methionine indicate a reduced D1 synthesis rate. Here, we show that VIGS-OHP1 plants are more susceptible towards elevated light intensities than control plants. This underlines an obligatory function of OHP1 for light acclimation.